Localization of the motor neuron somata of the median nerve in albino rat - Rathna, B.S.; Ullah, Madyamuzammil; Mansor, Othman (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Introduction: The position of the median motomuclei and also the rostral and caudal limits of the location of motor neuron somata of median nerve in the spinal cord has been investigated Methodology: . Twelve Albino rats ( Sprague -Dawley) of either sex were used in the study and divided into two groups, Gp 1 & Gp 11 . GROUP-l:The animals of this group further divided into two subgroups (GplA and Gp1B) Under general anaesthesia (Nembutal sodium at a dose of30 mg I kg. weight intraperitonealy), the right median nerve was exposed in the axilla, cut and a part of it removed to prevent reunion. In other group the right median nerve was exposed just above the wrist before it gives any branch and a portion removed to prevent reunion . The left side acted as control. The animals were sacrificed 3 - 5 weeks after operation, circulation was flushed with normal saline and perfused with 10 % formal saline at a pressure of 125mm Hg. The 5th,6th, 7th, 8th, cervical and 18 \ and 2nd, thoracic segments of the spinal cord were removed by dorsal approac~ separated from each other and embedded in paraffm. Their serial sections were cut at 40 micrometers and stained with thionine for nissl granules. The sections were examined microscopically to identify the chromatolysed neuron somata. From the the transverse serial sections a reconstruction of the cell column was made. GROUP - 11: In this group , the motor neuron somata was localized by using the horseradish peroxidase (HRP). The right median nerve was cut in the axilla under general anaesthesia (like above) and its proximal stump will be put in a small container filled with HRP (30%) for 90 minutes.After 48-72 hours of survival, the animals were reanaesthetized and perfused transcardially with saline followed by fixative ( o.5o/o paraformaldehyde, 1.25% glutaraldehyde, Ph 7.2 ) and fixative containing sucrose (30o/o ). The 5th, 6th, 7th, 8th, cervical and 1st and 2nd thoracic segments of the spinal cord were removed and transverse frozen sections were cut at 60 microns with a cryostat treated with tetramethyl benzidine .The sections were examined microscopically for tracer positive somata and their locations. from the serial transverse sections a reconstruction of cell columns was made. Results: In those animals in which median nerve cut in the axilla: Chromatolysed neuron were observed in the 6th , 7th ,& gth cervical & 1st thoracic segments of the spinal cord. Those animals in which median nerve was cut at wrist: chromatolysed neuron were observed in the gth cervical & 1st thoracic segments or" the spinal cord. Horseradish peroxidase(HRP) technique: HRP was ap~lied to the proximal cut end of median nerve in the axilla.HRP-labeled cells seen in 6th 7th gth and 1st thoracic segments of the spinal cord. HRP was applied to the proximal cut end of median nerve at the wrist. HRP- labeled cells were observed in gth and 1st thoracic segments of the spinal cord. Conclusions: The motor neuron somata of median nerve in Albino rat are located in the 6th 7th g1h and 1st thoracic segments of spinal cord. In 6th and 7th segments neurons were located in the dorsolateral(DL) and retrodorsolateral (RDL) cell columns of the ventral grey horn of spinal cord. Median nerve supplying the hand muscles are located only in the retrodorsal (RDL) cell colunn of ventral grey hom of 8th cervical and 1st thoracic segments of spinal cord.